Metal–Organic Polyhedra Cages Immobilized on a Plasmonic Substrate for Sensitive Detection of Trace Explosives. (31st August 2015) - Wang, Chen; Shang, Jin; Lan, Yue; Tian, Tian; Wang, Hui; Chen, Xi; Gu, Jing‐Ying; Liu, Jefferson Zhe; Wan, Li‐Jun; Zhu, Wei; Li, Guangtao
Abstract : A novel strategy for highly sensitive detection and discrimination of explosives is developed based on the metal–organic polyhedra (MOP)‐decorated plasmonic substrate. It is found that the careful selection of the geometric and electronic characteristics of the assembly units (organic ligands and unsaturated metals sites) embedded within the MOP cage allows for the integration of multiple weak molecular interactions in a controllable fashion and thus the MOP cage can serve as an excellent receptor for selective uptake and binding of explosives. By further grafting of the MOP cage onto a plasmonic substrate with good surface‐enhanced Raman scattering enhancement factor, the resulting sensor shows a good sensing capability to various groups of ultratrace explosives, especially the challenging aliphatic nitro‐organics. Abstract : A novel strategy for highly sensitive detection and discrimination of explosives is developed based on a metal–organic polyhedra (MOP)‐decorated plasmonic substrate. MOP can serve as a receptor for selective uptake and binding of explosives. Grafting of the MOP onto a plasmonic substrate with good surface‐enhanced Raman scattering enhancement factor, the sensor shows excellent discrimination power toward explosives.